2016
DOI: 10.1021/acs.langmuir.6b02890
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polymeric Films from Microbubbles Generated Using a T-Junction Microfluidic Device

Abstract: In this work, a simple microfluidic junction with a T geometry and coarse (200 μm diameter) capillaries was used to generate monodisperse microbubbles with an alginate polymer shell. Subsequently, these bubbles were used to prepare porous alginate films with good control over the pore structure. The lack of pore size, shape, and surface control in scalable forming of polymeric films is a major application-limiting drawback at present. Controlling the thinning process of the shell of the bubbles to tune the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
3
23
1
Order By: Relevance
“…Well-ordered porous scaffolds refer to those have highly ordered microporous textures with regular pore shape, uniform pore size and ordered pore arrangement. Recent literature reports indicated that well-ordered porous structures performed better in the study of cellular behaviors than disordered porous scaffolds [ 25 , 27 , 32 , 49 ]. In this short review, two kinds of well-ordered porous scaffold are detailed introduced, including 2D film-like scaffolds and 3D foam-like scaffolds.…”
Section: Well-ordered Porous Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-ordered porous scaffolds refer to those have highly ordered microporous textures with regular pore shape, uniform pore size and ordered pore arrangement. Recent literature reports indicated that well-ordered porous structures performed better in the study of cellular behaviors than disordered porous scaffolds [ 25 , 27 , 32 , 49 ]. In this short review, two kinds of well-ordered porous scaffold are detailed introduced, including 2D film-like scaffolds and 3D foam-like scaffolds.…”
Section: Well-ordered Porous Scaffoldsmentioning
confidence: 99%
“…Tailoring the morphology of the macroporous structure remains one of the biggest challenges in the preparation process of scaffolds. In recent decades, numerous studies have sought to control pore size and size distribution to create well-ordered porous scaffolds by emerging approaches [ 25 , 26 , 27 , 28 , 29 , 30 ], and their advantages and limitations are summarized in Table 2 . Among them, a templating method based on evaporative cooling, which was called breath figure, was applied to produce well-ordered porous films [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ordered porous films. Based on the previous studies 303 on the influence of different parameters on the bubble bursting process, in 2016, Elsayed et al 304 introduced a one-step fabrication approach with a simple microfluidic junction to synthesize ordered porous films. In brief, by adjusting the gas pressure via a digital manometer and the flow rate of the polymeric solution, highly monodispersed bubbles with different sizes were firstly generated in T-junction microfluidic capillaries.…”
Section: Ordered Macroporous Particlesmentioning
confidence: 99%
“…As indicated in Figure 15 b, HepG2 and 3T3 were co-cultured for seven days in the uniform film of 100 μm in thickness and several millimeters in width, and formed micro-organoids similar to the structure of in vivo hepatic cord. To overcome previous limitations in the scalable formation of polymeric films, such as lack of pore size, shape, and surface control, Elsayed et al introduced a microfluidic junction and coarse capillaries to synthesize ordered porous films [ 113 ]. Highly monodispersed bubbles were firstly generated in T-junction microfluidic capillaries.…”
Section: Sheet Biomaterials Synthesis and Applicationsmentioning
confidence: 99%